Faktor - Faktor Yang Berhubungan Dengan Pengetahuan Siswa Kelas VIII Tentang Bullying Di SMP Negeri 05 Kota Bengkulu Tahun 2024 - Yugita, Ira; Hermiati , Dilfera; Tranado, Hengki (Jurnal Multidisiplin, 2025)
Schools are institutions that provide education for children and adolescents are required to play an active role in dealing with juvenile delinquency, and usually counselors in schools are fully as core personnel in guidance and counseling services and directly have the task of dealing with juvenile delinquency problems in schools (Musbikin, 2020). The method used in this research is survey research with a descriptive approach method with a cross sectional design, namely the cause variable (independent) and the dependent variable (dependent) are measured and collected at the same time by means of approach, observation, and data collection at the same time the data is collected by distributing questionnaires to 78 respondents of SMPN 05 of Bengkulu City students, sampling technique using purposive random sampling. The results of univariate analysis showed that almost some respondents (28.2%) had poor social culture, most respondents (71.8%) had good social culture, some respondents (33.3%) with poor social media, most respondents (66.7%) with good social media, and some respondents (35.9%) with poor experience, most respondents (64.1%) with good experience. The results of bivariate analysis there is a correlation between social culture with 8th grade students' knowledge about bullying where the p value is (0.000), there is a correlation between social media with 8th grade students' knowledge about bullying where the p value is (0.029), there is a correlation between experience with 8th grade students' knowledge about bullying where the p value is (0.000). Researchers suggest that for SMPN 05 of Bengkulu City the results of this study can provide a basis for implementing guidance, coaching, and counseling activity programs on bullying.